Peran Pembelajaran Steam Dalam Meningkatkan Perkembangan Kognitif Anak Usia Dini 4-6 Tahun - Desi Alyani Liufeto; Yeni Felpina Lasena; Apriani Aplunggi; Elias Matias Laure; Selfi Jerwanti Bako; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Early childhood e ducation is an essential effort to optimize children’s holistic development from birth to six years old, including cognitive development. Cognitive development in children aged 4–6 years plays a crucial role in shaping thinking skills, concept understanding, memory, and problem-solving abilities. One learning approach considered effective in stimulating children’s cognitive development is STEAM learning (Science, Technology, Engineering, Art, and Mathematics). This study aimed to examine the effect of STEAM learning on the cognitive development of children aged 4–6 years at PAUD Bet’El Naimata, Kupang City. This research employed a quantitative method with an ex-post facto design. The research subjects consisted of 20 children selected using a total sampling technique. Data were collected using validated and reliable instruments and analyzed using descriptive analysis and simple linear regression with SPSS version 25.0. The results showed that STEAM learning was in the high category (55%), while children’s cognitive development was generally in the moderate to high category. Regression analysis indicated a significance value of 0.004 < 0.05, meaning that STEAM learning had a positive and significant effect on the cognitive development of children aged 4–6 years, contributing 20.7% to cognitive development. Therefore, it can be concluded that STEAM learning is effective in enhancing early childhood cognitive development through active, exploratory, and meaningful learning experiences